Processing Plausibility in Concessive and Causal Relations: Evidence from Self-Paced Reading and Eye-Tracking. Issue 4 (20th April 2020) - Lyu, Siqi; Tu, Jung-Yueh; Lin, Chien-Jer Charles
ABSTRACT: In this study participants read plausible and implausible sentences containing concessive and causal relations in Chinese, for instance, [Although/Because] he has a talent for language, he [doesn't like/likes] learning English . In two self-paced reading experiments (Experiments 1 and 2), we consistently found the plausibility effect at the postcritical region in both concession and causality. When a second postcritical region was added (Experiment 2), implausibility induced a sustained effect in causality but became temporarily acceptable in concession. In an eye-tracking study, plausibility induced a larger effect in concession on the second-pass and the total reading time of the precritical regions than in causality. The results suggest that verifying sentence plausibility in a negated cause–effect relation (i.e., concession) can be as fast as in a direct cause–effect relation (i.e., causality), as negation is expected in processing concession. At a later stage, different strategies are adopted in resolving the implausibility of the two relations. We suggest that a perspective shift is involved in resolving the implausibility in concession, which induces greater cost compared with causality.